Laparoscopic-assisted percutaneous endoscopic gastrostomy in two patients who failed percutaneous endoscopic gastrostomy. (2015) - Abbassi, Ziad; Naiken, Surennaidoo P.; Buchs, Nicolas C.; Staszewicz, Wojciech; Giostra, Emiliano; Morel, Philippe
Highlights: Gastrostomy can be a necessity in a variety of clinical situations either for nutrition or for gastrointestinal discharge. There are two major techniques: open gastrostomy and minimally invasive gastrostomy. We describe herein a technique of laparoscopic-assisted percutaneous endoscopic gastrostomy (LAPEG) in 2 cases with different primary pathologies and unsuccessful attempt of Percutaneous endoscopic gastrostomy as the first intention. LAPEG might be an interesting option by minimizing the risk of intestinal injury and might be a faster and easier procedure than laparoscopic gastrostomy, and should be considered for selected cases. Abstract: Introduction: Percutaneous endoscopic gastrostomy (PEG) is a common procedure to obtain a feeding tube. However, this technique might imply several difficulties and complications. The inability to transilluminate the abdominal wall may occur frequently, especially in obese or multi-operated patients. With the emergence of minimally invasive surgery, laparoscopic-assisted percutaneous endoscopic gastrostomy (LAPEG) might provide a safe and efficient alternative. Presentation of cases: We report hereby two cases of patients having undergone LAPEG in our institution. Conventional PEGs were deemed impossible because of the absence of transillumination and motivated a surgical approach. Two obese patients with a Body Mass Index (BMI) of 31 and 45 kg/m 2 respectively presented neurological condition (stroke and Parkinson's disease) requiring a feeding tube. While a PEG was unsuccessful (impossibility to transilluminate), a LAPEG was attempted. The procedure and the recovery were uneventful. Discussion: There are different techniques for gastrostomy tube placement: open gastrostomy, PEG and radiologic procedure. The PEG is associated with a significant risk of bowel perforation. LAPEG seems to be an interesting option in order to avoid an open gastrostomy in patients in whom a PEG cannot be performed. This is especially true in obese patients, where a transillumination cannot be performed. It offers an endoscopic view of the stomach simultaneously to the laparoscopic approach that allows a potential decrease of major complications. Conclusion: While the literature reports mainly pediatric cases, we present herein two successful LAPEG in adult obese patients. In case of impossibility to perform PEG, this technique allows a safe direct visualization of the stomach and other adjacent organs.